2015
DOI: 10.1159/000435887
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision-Making, Control Preferences and Psychological Well-Being in Patients with RPE65 Deficiency Awaiting Experimental Gene Therapy

Abstract: Purpose: Retinal gene therapy trials are currently ongoing in a small number of inherited retinal disorders and this number is expected to rise significantly. The aim of this study was to analyze the psychological aspects of patients with RPE65 deficiency awaiting potential enrollment in gene therapy trials. Methods: Five patients with genetically proven RPE65 deficiency took part in this study. They were asked to complete the German versions of (i) the Patient Health Questionnaire (PHQ-D), (ii) the National E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
(26 reference statements)
0
12
0
1
Order By: Relevance
“…Twenty-four of these papers related specifically to cell therapy while 11 pertained to gene therapy. Five of the included studies were conducted in the UK [12][13][14][15][16] , eight in the USA [17][18][19][20][21][22][23][24] , six in Canada [25][26][27][28][29][30] , two were conducted in Australia 31,32 and one each from Belgium 33 , China 34 , Germany 35 , Hungary 36 , Ireland 37 , Japan 38 , Korea 39 , South Korea 40 and Sweden 41 . One study included multiple countries across Europe 42 , three studies were set in Canada and USA [43][44][45] and one included Europe, USA and Canada 46 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-four of these papers related specifically to cell therapy while 11 pertained to gene therapy. Five of the included studies were conducted in the UK [12][13][14][15][16] , eight in the USA [17][18][19][20][21][22][23][24] , six in Canada [25][26][27][28][29][30] , two were conducted in Australia 31,32 and one each from Belgium 33 , China 34 , Germany 35 , Hungary 36 , Ireland 37 , Japan 38 , Korea 39 , South Korea 40 and Sweden 41 . One study included multiple countries across Europe 42 , three studies were set in Canada and USA [43][44][45] and one included Europe, USA and Canada 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Participants with human immunodeficiency virus (HIV), in a study, were aware of the potential application of gene therapy in conditions like Parkinson's disease, yet few knew about its potential use in HIV/AIDS treatment 19 . A study conducted with a few young adults reported high levels of awareness of gene therapy 35 . The male gender and higher educational degrees were also associated with a higher level of knowledge on cell therapies in a mixed population of cancer patients and members of the public 33 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Weitergehende Übersichtsartikel zu den therapeutischen Strategien der Gentherapie wurden in deutscher Sprache im "Ophthalmologen" [2] sowie der "Zeitschrift für praktische Augenheilkunde" publiziert [13]. Die psychologische Situation der Patienten in Anbetracht der Möglichkeit einer Gentherapie wurde in einem Artikel von Nelles und Kollegen diskutiert [14].…”
Section: Kernaussagen Der Stellungnahmeunclassified